X-Ray classification to detect COVID-19 using ensemble model - Solaiman, Ishmam Ahmed; Sanjana, Tasnim Islam; Sobhan, Samila; Maria, Tanzila Sultana (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.